EFEKTIVITAS STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH PADA MATERI PROGRAM LINEAR DI SMA - Nurhidayah, Nurhidayah; Halini, Halini; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research aims to know and describe the effectiveness of strategies active learning with index card match type in the linear programming topic the grade XI MIPA 2 of SMAN 6 Pontianak. There were three indicators that were used to determined the effectiveness of strategies active learning with index card match type such: implementation of learning, studen’s learning activities, and student’s learning outcome reached classical. The research method use is experimen method. There were two techniques to collecting data, that’s are measurement and observation techniques. The research subject is class XI MIPA 2 of SMAN 6 Pontianak. Based on the data analysis that review three indicators, the result are: (1) implementation of learning categorized good  with average score 3,28; (2) studen’s learning activities  categorized active with average score 75%; (3) student’s learning outcome is not reached classical completeness with only 65,6% of student can achieve the minimum completeness criteria. Because only two out of three indicators that achieved. It means that the effectiveness of strategies active learning with index card match type not effective to aply in the linear programming topic the grade XI MIPA 2 of SMAN 6 Pontianak. Keywords: Effectiveness, Strategies active learning with index card match,                                                          Linear programming.